2014
DOI: 10.1002/anie.201409961
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene Catalyzed Enantioselective α‐Fluorination of Aliphatic Aldehydes and α‐Chloro Aldehydes: Synthesis of α‐Fluoro Esters, Amides, and Thioesters

Abstract: The asymmetric fluorination of azolium enolates that are generated from readily available simple aliphatic aldehydes or α-chloro aldehydes and N-heterocyclic carbenes (NHCs) is described. The process significantly expands the synthetic utility of NHC-catalyzed fluorination and provides facile access to a wide range of α-fluoro esters, amides, and thioesters with excellent enantioselectivity. Pyrazole was identified as an excellent acyl transfer reagent for catalytic amide formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…Despite advances, these transformations commonly suffered from harsh reaction conditions, the use of costly metal catalysts, stoichiometric oxidants, and extra additives, which constitute drawbacks for large-scale applications and late-stage modifications. 11 Alternatively, N-heterocyclic carbenes (NHCs) derived from thiazolium ions have the capability to accomplish the oxidative esterification with the assistance of various oxidants, such as MnO 2 , 12 nitroarene, 13 TEMPO, 14 NFSI, 15 diphenoquinone, 16 azobenzene, 17 phenazine, 18 CCl 3 CN, 19 and O 2 /air ( Scheme 1B ). 20 From a viewpoint of green chemistry, a metal-free NHC-catalyzed one-pot esterification of aldehydes under air has become more sought after.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances, these transformations commonly suffered from harsh reaction conditions, the use of costly metal catalysts, stoichiometric oxidants, and extra additives, which constitute drawbacks for large-scale applications and late-stage modifications. 11 Alternatively, N-heterocyclic carbenes (NHCs) derived from thiazolium ions have the capability to accomplish the oxidative esterification with the assistance of various oxidants, such as MnO 2 , 12 nitroarene, 13 TEMPO, 14 NFSI, 15 diphenoquinone, 16 azobenzene, 17 phenazine, 18 CCl 3 CN, 19 and O 2 /air ( Scheme 1B ). 20 From a viewpoint of green chemistry, a metal-free NHC-catalyzed one-pot esterification of aldehydes under air has become more sought after.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most common reactive intermediates generated using NHCs, the azolium enolate has been widely used [27,28]. Methods to generate azolium enolates from a number of precursors have been reported, including the use of ketenes [29,30], α-functionalized aldehydes [31][32][33][34][35], enals [36][37][38], aryl esters [39][40][41][42], or aldehydes [43][44][45] in the presence of an oxidant. As representative examples of the use of azolium enolates in reactions with trifluoroacetophenone derivatives, Ye and co-workers have shown that using disubstituted ketenes as azolium enolate precursors and NHC precatalyst 1 allowed access to trifluoromethyl-substituted β-lactone products in a high yield, diastereo-, and enantioselectivity ( Figure 2A) [46].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, asymmetric fluorination of carbonyl compound is undoubtedly one of the most significant transformations. In contrast to asymmetric construction of α-fluoro aldehyde, ketone, or 1,3-dicarbonyl derivatives, the development of methods for highly enantioselective synthesis of α-fluoro carboxylic acid derivatives lags behind. Despite some elegant approaches developed in this context, there are still some limitations with existing methods such as the need to use high active carbonyl compounds (aldehydes and its analogies) ,, or unstable intermediates (ketenes) (Scheme a).…”
mentioning
confidence: 99%